Endovascular treatment of spontaneous isolated abdominal aortic dissection - Giribono, Anna Maria (Acta Radiol Open, 2016)
Isolated abdominal aortic dissection is a rare clinical disease representing only 1.3% of all dissections. There are a few case series reported in the literature. The causes of this pathology can be spontaneous, iatrogenic, or traumatic. Most patients are asymptomatic and symptoms are usually abdominal or back pain, while claudication and lower limb ischemia are rare. Surgical and endovascular treatment are two valid options with acceptable results. We herein describe nine cases of symptomatic spontaneous isolated abdominal aortic dissection, out of which four successfully were treated with an endovascular approach between July 2003 and July 2013. All patients were men, smokers, symptomatic (either abdominal or back pain or lower limb ischemia), with a history of high blood pressure, with a medical history negative for concomitant aneurysmatic dilatation or previous endovascular intervention. Diagnosis of isolated abdominal aortic dissection were established by contrast-enhanced computed tomography angiography (CTA) of the thoracic and abdominal aorta. All nine patients initially underwent medical treatment. In four symptomatic cases, non-responsive to medical therapy, bare-metal stents or stent grafts were successfully positioned. All patients completed a CTA follow-up of at least 12 months, during which they remained symptom-free. Endovascular management of this condition is associated with a high rate of technical success and a low mortality; therefore, it can be considered the treatment of choice when it is feasible.